Dialektika Pengangkatan Menteri Perspektif Al Mawardi dan Ibn Khaldun - Fuad Hasim; Saadatul Maghfira (Universitas Sebelas Maret, 2024)
The appointment of ministers according to Imam Al-Mawardi and Ibn Khaldun is examined dialectically in this work. The issues found are how Imam Al-Mawardi defines the form of ministerial appointment, how Ibn Khaldun defines the form of ministerial appointment and how Imam Al-Mawardi and Ibn Khaldun argue about the form of ministerial appointment. This research, which is a library research using the Comparative Approach method, examines the dialog between Imam Al-Mawardi and Ibn Khaldun about the appointment of ministers. The findings of this study present a dialectical comparison between Imam Al-Mawardi and Ibn Khaldun regarding the review of Islamic constitutional law regarding the appointment of ministers. From the research results it is evident that Imam Al-Mawardi and Ibn Khaldun have very different perspectives on this issue, with Imam Al-Mawardi explaining in detail and clearly through his dialectic about how the legal requirements up to the appointment of a minister and the division of ministers in terms of their duties and responsibilities as servants of the caliph. Although what Ibn Khaldun says is obvious in this discussion of ministerial appointments, he provides an overview of the role of a minister in a state as well as the standards that govern ministerial appointments. Despite the variety of terminology used to express them, they all come to the same conclusion: set criteria and circumstances must be followed when a minister is nominated.